Basque-language literacy in rural schools in the Basque Country (1900-1939) - Garmendia Larrañaga, Joxe (Historia y Memoria de la Educación, 2018)
In the first third of the twentieth century, the Basque Country underwent a modernizing process that affected general education. Given that there were still high rates of illiteracy in rural areas and the populations were Basque-speaking, in an attempt to increase literacy the provincial councils of Bizkaia and Gipuzkoa put two different programmes into motion. Bizkaia established «escuelas de barriada», or neighbourhood schools (1919-1938), and Gipuzkoa instituted the rural provincial schools (1930-1938). Although the neighbourhood schools in Bizkaia began by trying to create Basque schools that were bilingual, political changes influenced the project. In the case of the provincial schools in Gipuzkoa, the goal was to combat the lack of instruction. The objective of this study is to compare these two rural literacy programmes in which literacy in Spanish and in Basque were intertwined